PENGEMBANGAN BAHAN AJAR MEKANIKA I BERBASIS E-LEARNING UNTUK MENGEMBANGKAN KEMANDIRIAN MAHASISWA - Yulianti, Dwi (Universitas Negeri Semarang, 2011)
This study aims to develop teaching materials Mechanics I-based e-learning to develop independence in physics education students Prodi. Modified study design development. Trials of teaching materials last six meetings. The results obtained appropriate teaching materials developed can be used to develop independence in learning and improve learning outcomes of cognitive, affective and psychomotor student of physics education Prodi FMIPA Unnes rombel 2 years 2009/2010